Genomic disparity impacts variant classification of cancer susceptibility genes in Turkish breast cancer patients - Nihat B. Agaoglu; Busra Unal; Connor P. Hayes; McKenzie Walker; Ozden Hatirnaz Ng; Levent Doganay; Nisan D. Can; Huma Q. Rana; Arezou A. Ghazani (Cancer Medicine, 2024)
Abstract Objective Turkish genome is underrepresented in large genomic databases. This study aims to evaluate the effect of allele frequency in the Turkish population in determining the clinical utility of germline findings in breast cancer, including invasive lobular carcinoma (ILC), mixed invasive ductal and lobular carcinoma (IDC‐L), and ductal carcinoma (DC). Methods Two clinic‐based cohorts from the Umraniye Research and Training Hospital (URTH) were used in this study: a cohort consisting of 132 women with breast cancer and a non‐cancer cohort consisting of 492 participants. The evaluation of the germline landscape was performed by analysis of 27 cancer genes. The frequency and type of variants in the breast cancer cohort were compared to those in the non‐cancer cohort to investigate the effect of population genetics. The variant allele frequencies in Turkish Variome and gnomAD were statistically evaluated. Results The genetic analysis identified 121 variants in the breast cancer cohort (actionable = 32, VUS = 89) and 223 variants in the non‐cancer cohort (actionable = 25, VUS = 188). The occurrence of 21 variants in both suggested a possible genetic population effect. Evaluation of allele frequency of 121 variants from the breast cancer cohort showed 22% had a significantly higher value in Turkish Variome compared to gnomAD (p < 0.0001, 95% CI) with a mean difference of 60 times (ranging from 1.37–354.4). After adjusting for variant allele frequency using the ancestry‐appropriate database, 6.7% (5/75) of VUS was reclassified to likely benign. Conclusion To our knowledge, this is the first study of population genetic effects in breast cancer subtypes in Turkish women. Our findings underscore the need for a large genomic database representing Turkish population‐specific variants. It further highlights the significance of the ancestry‐appropriate population database for accurate variant assessment in clinical settings.